Inhibition of the inflammasome ameliorates orthologous polycystic kidney disease - Junwei Liu; Manuel Rogg; Katharina Moos; Shaya Sasanpour; Vera Strassl; Manaswita Jain; Sato Magassa; Björn Neubauer; Simone Braeg; Benedikt S. Saller; Lisa Weißer; Frank Bienaimé; et al. (Proceedings of the National Academy of Sciences, 2025)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic kidney disease. Limited treatment options lead to renal failure in the vast majority of affected individuals. Novel therapeutic approaches are needed. Recent evidence has identified inflammation as an important driver of ADPKD. We analyzed transcriptional profiles in an orthologous Pkd1 mouse model and found a strong upregulation of the inflammasome pathway. To investigate the role of inflammasomes on cyst formation and kidney function, we modulated inflammasome activity through genetic targeting of the essential inflammasome component Pycard/Asc or treatment with the inflammasome inhibitor MCC950. Genetic deletion of Pycard/Asc in Pkd1 mutant mice significantly reduced cyst formation, and kidney function was improved. Reductions were seen in inflammation, fibrosis, and urinary excretion of IL-18. Analogous results were obtained through tubule-specific inactivation of Pycard/Asc or treatment of Pkd1 mutant mice with the inflammasome inhibitor MCC950. These findings demonstrate that inflammasomes act as drivers of disease severity in an orthologous mouse model of ADPKD. We pinpoint a separate, epithelial pool of inflammasomes in the diseased kidney and identify inflammasome inhibition as a promising strategy for the treatment of ADPKD.